Effect of humic-acid fouling on membrane distillation - Tan, Yong Zen (2017)
Membrane distillation (MD) can concentrate non-volatile solutes or remove volatiles and dissolved gases from an aqueous feed. A microporous hydrophobic membrane provides a barrier between the hot feed and cold distillate. Although MD can operate at ambient pressure and moderate temperatures, use waste heat, and treat wastewater via an MD-bioreactor, it has problems such as temperature polarization, liquid weeping to the distillate side, and membrane fouling. Prior studies speculated that fouling can add a heat- or mass-transfer resistance, or cause a vapor-pressure reduction owing to the Kelvin effect, but did not isolate these effects. This study confirms that the vapor-pressure depression owing to the concave interface in the small pores of the fouling layer is a dominant cause of the 25–63% flux reduction observed for humic-acid fouling on PTFE and PVDF membranes. This study underscores the importance of selecting MD membranes based on their pore-size distribution rather than just their nominal diameter in order to maximize the contribution of Knudsen diffusion. It suggests the development of dual-layer membranes having a thin hydrophilic layer with relatively large pores overlying a hydrophobic layer with a typical MD membrane structure in order to mitigate the vapor-pressure reduction owing to membrane fouling.